"Pretty Pressure" From Peers, Parents, and the Media: A Longitudinal Study of Appearance‐Based Rejection Sensitivity. (24th March 2017) - Webb, Haley J.; Zimmer‐Gembeck, Melanie J.; Waters, Allison M.; Farrell, Lara J.; Nesdale, Drew; Downey, Geraldine
Abstract : Drawing from the tripartite sociocultural model of body image, the researchers examined whether direct messages and modeling from peers, parents, and media were concurrently and prospectively associated with appearance‐based rejection sensitivity (appearance‐RS) in young adolescents ( M age  = 12.0 years). Appearance‐RS was higher among those who concurrently reported more appearance‐related teasing and pressure by peers, more parent teasing, and greater acceptance of media appearance ideals. In prospective analyses, greater increases in appearance‐RS over 1 year were found for adolescents who perceived higher levels of parental appearance‐related teasing and negative attitudes about their own appearance. Moderation analyses indicated the positive prospective association between parental negative appearance attitudes and appearance‐RS was found in younger but not older participants. Gender did not moderate associations.